Larval and adult diet affect phenotypic plasticity in thermal tolerance of the marula fly, Ceratitis cosyra (Walker) (Diptera: Tephritidae) - Pullock, Dylan A.; Malod, Kévin; Manrakhan, Aruna; Weldon, Christopher W. (Frontiers in Insect Science, 2023)
Temperature fluctuations are important for the distribution and survival of insects. Rapid hardening, a type of phenotypic plasticity, is an adaptation that can help individuals better tolerate lethal temperatures because of earlier exposure to a sublethal but stressful temperature. Nutrition and sex are also known to influence a species ability to tolerate thermal stress. This study determined the effects of larval diet, adult diet, sex and hardening on the thermal tolerance of Ceratitis cosyra (Diptera: Tephritidae) at lower and upper lethal temperatures. Larvae were raised on either an 8% torula yeast (high) or a 1% torula yeast (low) larval diet and then introduced to one of three dietary regimes as adults for thermal tolerance and hardening assays: no adult diet, sugar only or sugar and hydrolysed yeast diet. Flies of known weight were then either heat- or cold-hardened for 2 hours before being exposed to a potentially lethal high or low temperature, respectively. Both nutrition and hardening as well as their interaction affected C. cosyra tolerance to stressful temperatures. However, this interaction was dependant on the type of stress, with nutrient restriction and possible adult dietary compensation resulting in improved cold temperature resistance only. The ability of C. cosyra to both compensate for a low protein larval diet and undergo rapid cold hardening after a brief exposure to sub lethal cold temperatures even when both the larva and the subsequent adult both fed on low protein diets indicates that individuals of the species have a better chance of survival in environments with extreme temperature variability, particularly at low temperatures. However, there appears to be limitations to the ability of C. cosyra to cold harden and the species may be more at risk from long term chronic effects than from any exposure to acute thermal stress.